PENGELOLAAN KOMPETENSI PEMILIK USAHA RUMAH MAKAN TRADISIONAL KELAS C DI KAWASAN WISATA PANTAI ANYER DAN PANTAI CARITA PROVINSI BANTEN - Maria BF Manalu (Eduturisma, 2016)
The restaurant business in the district of Serang and Pandeglang is very potential to develop, especially for supporting culinary tourism. The presence of C-class traditional restaurant business’ owners (abbreviated to PURMT / C) are needed to accommodate the customers’ needs of foods. Mostly, PURMT / C in the district of Serang and Pandeglang still adopt traditional way of cooking as a legacy of the their ancestor and self sorted kinds of meals. Customers, on the contrary, expect more deverse foods, better food service and more sanitary environment. Efforts to improve the competencies have not shown optimal results due to lack of supports from government, culinary organizations and tourism counselling. This study aims to describe the profile of PURMT / C and their level of competence in the coastal resort area of ​​Anyer and Carita beaches of Banten Province. Data analysis used descriptive statistics. The results show that: (1) The majority of PURMT / C are in productive ages (28-35 years) and have high motivation to support a household. Their strong motivation encourage the development of competence by themselves. (2) Lack of supports from governments, culinary organizations and tourism counselling were considered. It effects that the development of culinary competence of PURMT/C hasn’t got the maximum results. The role of government support, the organization of culinary and tourism counseling is, therefore, needed.